Uridine and its role in metabolic diseases, tumors, and neurodegenerative diseases - Yang, Yueyuan; Ye, Yahong; Deng, Yingfeng; Gao, Ling (Frontiers in Physiology, 2024)
Uridine is a pyrimidine nucleoside found in plasma and cerebrospinal fluid with a concentration higher than the other nucleosides. As a simple metabolite, uridine plays a pivotal role in various biological processes. In addition to nucleic acid synthesis, uridine is critical to glycogen synthesis through the formation of uridine diphosphate glucose (UDPG) in which promotes the production of UDP-GlcNAc in the hexosamine biosynthetic pathway (HBP) and supplies UDP-GlcNAc for O-GlcNAcylation. This process can regulate protein modification and affect its function. Moreover, Uridine has an effect on body temperature and circadian rhythms, which can regulate the metabolic rate and the expression of metabolic genes. Abnormal levels of blood uridine have been found in people with diabetes and obesity, suggesting a link of uridine dysregulation and metabolic disorders. At present, the role of uridine in glucose metabolism and lipid metabolism is controversial, and the mechanism is not clear, but it shows the trend of long-term damage and short-term benefit. Therefore, maintaining uridine homeostasis is essential for maintaining basic functions and normal metabolism. This article summarizes the latest findings about the metabolic effects of uridine and the potential of uridine metabolism as therapeutic target in treatment of metabolic disorders.